Celiac crisis in adults: a case report and review of the literature focusing in the prevention of refeeding syndrome - Marcela de-Almeida-Menezes; Vírginia Lúcia Ribeiro-Cabral; Sônia S. Lorena (Revista Espanola de Enfermedades Digestivas)
Introduction: Celiac crisis is a life-threatening complication of celiac disease that is rarely described in adults. Case report: We report the case of a 31-year-old man with celiac crisis as a first manifestation of celiac disease. The patient presented with severe diarrhea, metabolic acidosis, and electrolyte disturbances accompanied by electrocardiographic alterations. A satisfactory clinical response was obtained after the correction of electrolyte abnormalities, hydration, and nutritional support with a gluten-free diet according to recommendations for patients at high risk of refeeding syndrome. Discussion: Celiac crisis generally occurs in patients with no previous diagnosis of celiac disease. The physician should therefore be aware of this diagnosis and consider celiac crisis in cases of unexplained intense secretory diarrhea, metabolic acidosis and severe electrolyte alterations in adults. The risk of refeeding syndrome should be assessed when a gluten-free diet is introduced and treatment of celiac crisis should include prevention and management of this possible complication.